Does Privatization Hurt Workers? Lessons from Comprehensive Manufacturing Firm Panel Data in Hungary, Romania, Russia and Ukraine - J. David Brown; John S. Earle; Álmos Telegdy (Hungarian Academy of Sciences, Institute of Economics, Labour Research Department, 2005)
We analyze the effects of privatization on firm-level wages and employment in four transition economies. Contrary to workers' fears, our fixed effect and random trend estimates imply little effect of domestic privatization, except for a slight negative effect in Russia, and they provide some evidence of positive foreign effects on both wages and employment in all four countries. The negligible employment impact of domestic privatization results from effects on efficiency and scale that are large, positive, but offsetting in Hungary and Romania, and from small effects of both types in Russia and Ukraine. The positive employment and wage bill consequences of foreign ownership result from a substantial scale-expansion effect that dominates the efficiency effect.
Keywords: D21; G34; J23; J31; L33; P31; 330; privatization; employment; wages; foreign ownership; Hungary; Romania; Russia; Ukraine; Privatisierung; Eigentümer; Ausländisch; Lohn; Erwerbstätigkeit; Industrie; Transformationsstaaten; Ungarn; Rumänien; Russland; Ukraine